TULP2, a New RNA-Binding Protein, Is Required for Mouse Spermatid Differentiation and Male Fertility - Zheng, Meimei; Chen, Xu; Cui, Yiqiang; Li, Wen; Dai, Haiqian; Yue, Qiuling; Zhang, Hao; Zheng, Ying; Guo, Xuejiang; Zhu, Hui (Frontiers in Cell and Developmental Biology, 2021)
Spermatogenesis requires a large number of proteins to be properly expressed at certain stages, during which post-transcriptional regulation plays an important role. RNA-binding proteins (RBPs) are key players in post-transcriptional regulation, but only a few RBPs have been recognized and preliminary explored their function in spermatogenesis at present. Here we identified a new RBP tubby-like protein 2 (TULP2) and found three potential deleterious missense mutations of Tulp2 gene in dyszoospermia patients. Therefore, we explored the function and mechanism of TULP2 in male reproduction. TULP2 was specifically expressed in the testis and localized to spermatids. Studies on Tulp2 knockout mice demonstrated that the loss of TULP2 led to male sterility; on the one hand, increases in elongated spermatid apoptosis and restricted spermatid release resulted in a decreased sperm count; on the other hand, the abnormal differentiation of spermatids induced defective sperm tail structures and reduced ATP contents, influencing sperm motility. Transcriptome sequencing of mouse testis revealed the potential target molecular network of TULP2, which played its role in spermatogenesis by regulating specific transcripts related to the cytoskeleton, apoptosis, RNA metabolism and biosynthesis, and energy metabolism. We also explored the potential regulator of TULP2 protein function by using immunoprecipitation and mass spectrometry analysis, indicating that TUPL2 might be recognized by CCT8 and correctly folded by the CCT complex to play a role in spermiogenesis. Our results demonstrated the important role of TULP2 in spermatid differentiation and male fertility, which could provide an effective target for the clinical diagnosis and treatment of patients with oligo-astheno-teratozoospermia, and enrich the biological theory of the role of RBPs in male reproduction.